2005
DOI: 10.1111/j.1365-2133.2005.06679.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophytes can trigger cooperative (CAMP-like) haemolytic reactions

Abstract: Our results show, for the first time, that in principle a CAMP-like effect can occur with dermatophtyes. This is a new observation of potential relevance for the pathogenesis of skin infections. The membrane-damaging factors released by dermatophytes should be further analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
0
19
1
1
Order By: Relevance
“…In addition, we observed CAMP reactions between Dly and V. cholerae, S. agalactiae, R. equi, and Aeromonas schubertii CAMP factors. In S. agalactiae the second-step agent has been reported to be a ceramide-binding protein (42), whereas in R. equi it is a cholesterol oxidase (41). Since it has been demonstrated that deletion of the V. cholerae VCC gene leads to a total suppression of hemolysis (43), we suggest that the unknown CAMP factor produced by V. cholerae is indeed VCC.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, we observed CAMP reactions between Dly and V. cholerae, S. agalactiae, R. equi, and Aeromonas schubertii CAMP factors. In S. agalactiae the second-step agent has been reported to be a ceramide-binding protein (42), whereas in R. equi it is a cholesterol oxidase (41). Since it has been demonstrated that deletion of the V. cholerae VCC gene leads to a total suppression of hemolysis (43), we suggest that the unknown CAMP factor produced by V. cholerae is indeed VCC.…”
Section: Discussionmentioning
confidence: 94%
“…It has been demonstrated that cholesterol is required for different poreforming toxins to induce cytolysis, as is the case for V. vulnificus cytolysin (16,38), staphylococcal alpha-toxin (39), and V. cholerae VCC (36,40). Hydrolysis of choline head groups in membranes by sphingomyelinases has been demonstrated to facilitate access to cholesterol and elicit destruction of the membrane by second-step agents (37,41). We demonstrated in our study that Results from three independent groups of 5 animals each per strain tested were pooled and compared using a chi-square test.…”
Section: Discussionmentioning
confidence: 99%
“…CAMP‐like reactions were examined daily for 7 days. The presence of a distinct arrowhead of haemolysis at the intersection between the tester strain and the test Exophiala streaks was considered as positivity …”
Section: Methodsmentioning
confidence: 99%
“…Neben den Enzymen spielen vermutlich weitere potenziell pathogene mykotische Faktoren eine Rolle bei der Dermatophyteninvasion. Dazu gehören Xanthomegnin als ein Dermatophytentoxin, Mannane als immunosuppressive Faktoren [15], Hämagglutinine und Faktoren, die kooperative hämolytische Reaktionen auslösen können [16]. Antibiotisch wirksame Substanzen, die von Dermatophyten gebildet werden können [17], sind möglicherweise wichtig zur Behauptung der Pilze gegen die synchrone bakterielle Besiedlung.…”
Section: Jddg | 10˙2010 (Band 8)unclassified